2019
DOI: 10.1096/fj.201902347r
|View full text |Cite
|
Sign up to set email alerts
|

Mouse brain proteomics establishes MDGA1 and CACHD1 as in vivo substrates of the Alzheimer protease BACE1

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 92 publications
(226 reference statements)
0
13
0
Order By: Relevance
“…S5 L and M ). We also found that β-site APP cleaving enzyme 1 –mediated cleavage of the MDGA1 MAM domain did not influence APP binding ( 33 ) ( SI Appendix , Fig. S5 N and O ).…”
Section: Resultsmentioning
confidence: 72%
“…S5 L and M ). We also found that β-site APP cleaving enzyme 1 –mediated cleavage of the MDGA1 MAM domain did not influence APP binding ( 33 ) ( SI Appendix , Fig. S5 N and O ).…”
Section: Resultsmentioning
confidence: 72%
“…Approaches to proteomic investigation of rodent models have typically utilized whole brain homogenate samples or smaller manually dissected areas of localized disease progression (Deng et al, 2018;Njavro et al, 2020;Zheng et al, 2020). A strength of our approach includes the use of the novel rTg-DI rat model of microvascular CAA that largely reflects many of the pathological changes and cognitive deficits observed in humans with CAA and is largely devoid of any parenchymal fibrillar plaque deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Besides APP, more than 60 putative BACE1 substrates have been reported in vitro using proteomic analysis (14)(15)(16)(17). Among them, only a few have been validated to date as BACE1 substrates in vivo, including neuregulin-1, Jagged 1 (Jag1), βsubunits of voltage-gated sodium channel (VGSCβ), amyloid precursor protein-like protein 1 and 2 (APLP1, APLP2), seizure protein 6 (SEZ6), seizure 6-like protein (SEZ6L), L1, cell adhesion molecule L1 like (CHL1), VWFA and cache domain-containing protein 1 (CACHD1), and MAM domaincontaining glycosylphosphatidylinositol anchor protein 1 (MDGA1) (14,(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
mentioning
confidence: 99%